Assessment of spatiotemporal variability of bacterial pollution in Darbandikhan Lake and its tributaries in the Kurdistan Region of Iraq - Ghafur, Pshtiwan Gharib; Abdulrahman, Rozhan Faraidun (Sulaimani Journal for Pure and Applied Sciences, 2023)
This study was designed to assess the spatiotemporal variability of bacterial pollution in Darbandikhan Lake and its river resources in Iraq's Kurdistan Region. Seasonally, 25 samples (a total of 100 samples year-round) were collected and examined for aerobic plate count (APC), total coliform (TC) and fecal coliform (FC) in all samples. Descriptive statistics for physiochemical and microbiological variables and the Pearson correlation coefficient (r) were performed using the Statistical Package for the Social Sciences (SPSS) version 20 and OriginPro 2022b–Correlation Plot. GraphPad Prism v9 was used to determine statistical significance (p < 0.05), one-way ANOVA was used, followed by Tukey's multiple comparison tests. Results indicated positive correlations between microbiological and Al, Cu, EC, Fe, K, Mg, Na, NO3, PO4, SO4, T.Alk, TDS, TH, Turb and Zn in most of seasons at the < 0.01 and < 0.05 significance levels. Furthermore, microbiological characteristics had a strongly positive correlation in all seasons. Water resources are heavily contaminated with coliforms, especially in wet seasons. The inhabitant’s activities, untreated sewage and waste water, disposed waste, and livestock were the main contributors to this pollution, which in turn led to waterborne diseases, particularly diarrhea. Considering the above issues, the government should treat the water resources properly and take the required actions to solve this issue.
Keywords: Aerobic plate count E coli fecal coliform total coliform Darbandikhan Lake